Studies on a cell culture derived from hepatopancreas of tiger prawn Penaeus monodon - Manohar, B Murali; Vivek, K V; Kumanan, K (Indian Journal of Fisheries, 2011)
Hepatopancreatocytes from hepatopancreas of penaeid shrimp, monodon were cultured in artificial medium Leibovitz-15, supplemented with glucose and sodium chloride in vitro. Two different approaches for culturing of these cells were followed, i) Culturing, enzymatically disrupted cells and ii) Explant culture of small tissue fragments. The second approach of explant cultures was observed to be highly adva- ntageous as a monolayer was observed within 4-6 days of culture. On the whole, cells could be maintained for as long as 45 days with a maximum of 5 passages. On subculturing, generally one subpopulation of cells with high proliferative capacity was observed to be predominant. Morphological studies lead to the conclusion that these cells were embryonic cells from the tubular epithelium of hepatopancreas.